2016
DOI: 10.1016/j.meegid.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological and virological characteristics of the first detected human case of avian influenza A(H5N6) virus

Abstract: A human infection with novel avian influenza A H5N6 virus emerged in Changsha city, China in February, 2014. This is the first detected human case among all human cases identified from 2014 to early 2016. We obtained and summarized clinical, epidemiological, and virological data from this patient. Complete genome of the virus was determined and compared to other avian influenza viruses via the construction of phylogenetic trees using the neighbor-joining approach. A girl aged five and half years developed feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…The cases were from Yunnan (n = 2, January and July 2015) and Guangdong/Shenzhen (n = 3, December 2015 and January 2016). Similar to the first three patients in 2014 (Table S8) (Pan et al, 2016;Yang et al, 2015;Zhang et al, 2016), all the 2015 and 2016 cases had histories of exposure to poultry and/or visiting LPMs. Our 2015 strains (G1.2) were novel reassortants among H5 viruses, H6N6 and the entire internal gene set from H9N2/H7N9 ( Figure 5A; Table S7), whereas the isolates from 2014 (G2 and G1) were earlier reassortants between H5 viruses and H6N6.…”
Section: Features Of Human-infecting H5n6 Virusesmentioning
confidence: 63%
“…The cases were from Yunnan (n = 2, January and July 2015) and Guangdong/Shenzhen (n = 3, December 2015 and January 2016). Similar to the first three patients in 2014 (Table S8) (Pan et al, 2016;Yang et al, 2015;Zhang et al, 2016), all the 2015 and 2016 cases had histories of exposure to poultry and/or visiting LPMs. Our 2015 strains (G1.2) were novel reassortants among H5 viruses, H6N6 and the entire internal gene set from H9N2/H7N9 ( Figure 5A; Table S7), whereas the isolates from 2014 (G2 and G1) were earlier reassortants between H5 viruses and H6N6.…”
Section: Features Of Human-infecting H5n6 Virusesmentioning
confidence: 63%
“…While many patients with H5N6 disease have a severe clinical course associated with severe pneumonia, multiple organ dysfunction and acute respiratory distress syndrome [7,9,10], sometimes associated with dissemination to extra-pulmonary organs [9], some patients did undergo milder illness [33]. The detection of cytokines and chemokines at both the mRNA and protein levels showed that while the H5N6 viruses we tested were not as high inducers of pro-inflammatory cytokines as H5N1, they were more potent inducers of these cytokines than was H1N1pdm.…”
Section: Discussionmentioning
confidence: 99%
“…The A(H5N6) virus is a new reassortant strain that contains gene segments from A(H5N1) and A(H5N2). The first human A(H5N6) infection was reported in a 5‐year‐old girl who had visited a live poultry market in China in 2014 . Influenza A(H5N6) outbreaks in birds and poultry have been reported in Vietnam and mainland China since 2014.…”
Section: Avian Influenzamentioning
confidence: 99%